MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN DENGAN MENGGUNAKAN KARTU PASANGAN PADA ANAK KELOMPOK B TK DAMHIL KOTA GORONTALO - Martianty Nalole (Jurnal Inovasi, 2011)
The child ability in knowing the symbol of number is still low, is stil low because from the 20 child in action only 8 who knowing the symbol. It can recognize for the application of numbers symbol the child still not knowing the symbol of noun. Slow in matching the symbol of number using in pairs card. Hypotesis weather child goup B in kindergarter Damhil Knowing symbol number can improving with using pairs card? And the aim of this research is for improving the child ability knowing the symbol number with using pairs card at child group B in kindergarter Damhil Gorontalo state. Result of research at syclus I get 14 child or 70% from 29 child has been finished knowing the symbol number and 3 child or 15% nor yet. According to result of research get conclution that with using pairs card can improving the ability of symbol number at child of kindergarter Damhil Kota Gorontalo.